Differences In The Effects Of Shooting Training After Dribble And After Back Pass On The Shooting Ability Of Athletes Aged 12-14 In Ssb Disporasu In 2024 - Hulu, Dirman; Wiyaka, Ibrahim (Sean Institute, 2025)
Shooting is an important aspect in football, especially for children aged 14-15 years who are in the development phase of technique and tactical understanding. At the age of 14-15, the ability to shoot the ball into the goal not only plays a role in scoring goals but also builds self-confidence, decision-making skills, and contributions to the team. Mastery of good shooting techniques helps players understand their role in the game, especially in the position of attacker or attacking midfielder. Therefore, it is important for coaches to introduce various variations of shooting exercises that are appropriate to the age and abilities of the players. The purpose of this study was to determine the difference in the effect of shooting after dribble and after back pass training on the shooting ability of athletes aged 12-14 at SSB DISPORASU in 2024. The research method used is experimental research (treatment) with data collection techniques involving two independent variables and one dependent variable. Using statistical tests of normality, homogeneity and paired t-tests and unpaired t-tests for hypotheses. The population in this study were 39 SSB DISPORASU athletes. And sampling used a purposive sampling technique with several criteria so that a sample of 22 athletes was obtained. The results of this study are (1) There is an effect of shooting after dribble training on shooting ability in athletes aged 12-14 years at SSB DISPORASU, (2) There is an effect of shooting after back pass training on shooting ability in athletes aged 12-14 years at SSB DISPORASU, (3) Shooting after dribble training has a greater effect than shooting after back pass training on shooting ability in athletes aged 12-14 years at SSB DISPORASU.